Employee of the month (Lionsgate, 2007)
A beautiful new cashier gets the slacker employees working hard, when they find out she only dates guys who have won the coveted 'Employee of the Month' award.

Employee of the month (Lions Gate Home Entertainment, Lionsgate, Distributed by Lions Gate Home Entertainment, 2007)
Life for David Walsh is going exceptionally well, that is until things in his life take an unexpected turn. In one day, his fiancee dumps him, and the bank boss fires him. To top it off, David tries to leave work but gets caught in a bank robbery. And this is just to get the day started.

Cashiers (Blastoff! Readers Community helpers, ,, 2021)
"Developed by literacy experts for students in kindergarten through grade three, this book introduces cashiers to young readers through leveled text and related photos"--Provided by publisher"--
Shopping day , What are cashiers? , What do cashiers do? , What makes a good cashier?

Normal (Normal, ,, 2015)
A seemingly mild-mannered, neighborly man who kidnaps young women and holds them in a cage in his basement meets a grocery store checkout girl who becomes his ultimate target before he intends to cease his violent activities.